DEVELOPMENT OF SOFT SKILLS IN PRIMARY SCHOOL STUDENTS BASED ON NATIONAL VALUES - ABDURAKHMANOVA, Maira; SADUAKAS, Gulbanu; Baş, Özlem (Pedagogy and Psychology, 2025)
In modern education, the development of soft skills among primary school students is of particular importance, as these skills contribute to their successful social adaptation, cognitive development and personal growth. This study is aimed at identifying opportunities for integrating national values into the process of forming soft skills in primary school students. The analysis of educational strategies of the countries (Finland, Japan, South Korea, USA, China, India) is carried out and the experience of the Republic of Kazakhstan in this context is considered. The key national values of Kazakhstan (language, traditions, family values, historical memory, national games, religious and spiritual norms, respect for nature) and their impact on the development of soft skills such as critical thinking, emotional intelligence, communicative and social abilities are identified. The research is based on the methods of conceptual analysis, comparative analysis of educational systems, and methods of systematization and classification. In the course of the work, effective pedagogical methods were identified, including projectbased learning with an ethnocultural component, role-playing, mentoring, folk games and the study of national literature. The results of the study confirm that the inclusion of national values in the educational process not only promotes the development of soft skills, but also strengthens the national identity of students, making their education more meaningful and appropriate to the socio-cultural context of Kazakhstan. The results obtained can be useful for teachers, methodologists and developers of educational programs when creating innovative methods for the formation of soft skills in younger schoolchildren.